1990
DOI: 10.1002/ajmg.1320370304
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal and jumping translocations of 15q1→qter in Prader‐Willi syndrome

Abstract: We analyzed 33 cases of Prader-Willi syndrome (PWS) (including 2 personal observations) with translocations of 15q1----qter onto the terminals of different, apparently whole chromosomes. In all but one of the 23 informative cases the translocations was de novo. Thirty of the patients were unbalanced and 27 had a 45-chromosome constitution compatible with a 3:1 segregation. One balanced and 2 unbalanced translocations were jumping ones. The possible existence of actual non-reciprocal translocations in man is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
2
30
1
Order By: Relevance
“…[31][32][33][34] JT in such cases are, however, also cytogenetically different compared to hematologic malignancies -they preferentially involve other donor chromosome regions and are not trisomic for the jumping region. [31][32][33][34][35] Altogether, the widespread temporally heterogeneous breakpoints of the donor chromosome and the subtelomeric breakpoints on the recipient chromosomes indicate a complex origin of JT: the multiple clones most likely arose more or less simultaneously, followed by clonal selection. In this context, it is noteworthy that a small clone with +3 preceded the unbalanced JT.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] JT in such cases are, however, also cytogenetically different compared to hematologic malignancies -they preferentially involve other donor chromosome regions and are not trisomic for the jumping region. [31][32][33][34][35] Altogether, the widespread temporally heterogeneous breakpoints of the donor chromosome and the subtelomeric breakpoints on the recipient chromosomes indicate a complex origin of JT: the multiple clones most likely arose more or less simultaneously, followed by clonal selection. In this context, it is noteworthy that a small clone with +3 preceded the unbalanced JT.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 346 subjects who performed FISH and/or microsatellite analysis, 68.8% had a del15, 30.05% had a UPD15 and 1.15% had a de novo translocation involving chromosome 15. Of the latter, two cases with a nonreciprocal translocation leading to 15pter-q13 monosomy have previously been described [Rivera et al, 1990]. The remaining two patients showed a 45,XY,der(9)t(9;15)(q34, q12),-15 and a 45,XX,der(15)t(15;20)(q12;q13.3), -15 karyotype, respectively.…”
Section: Population Datamentioning
confidence: 96%
“…PWS then occurs via either paternally derived deletions or maternally derived uniparental disomy, each the result of abnormal meiotic segregation. A review by Rivera et al [1990] reported that only 1 of 19 informative cases with a complex abnormality of chromosome 15 was inherited, so it appears that most structural abnormalities in PWS result from de novo event during gametogenesis. The recurrence risk is thus expected to be very low.…”
Section: Other Cytogenetic Abnormalitiesmentioning
confidence: 99%